2008
DOI: 10.1007/s00056-008-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Microdamage in Cortical Bone due to the Overtightening of Orthodontic Microscrews

Abstract: We demonstrate that there was more microstructural damage in cortical bone due to overtightening through deep insertion of orthodontic microscrews than occurred at the lower insertion depth. Extensive osseous microdamage may detract from the stability of immediately-loaded microscrews and implants due to the bone-remodeling processes initiated by microdamage. The subject of just how serious this potential risk is should be addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 34 publications
3
41
0
1
Order By: Relevance
“…4,20,21,22 During exploration of this bone, it was observed that some characteristics such as color, texture and drill resistance differed in its various regions. Pubic bone was darker and more resistant when compared with iliac bone.…”
Section: Discussionmentioning
confidence: 99%
“…4,20,21,22 During exploration of this bone, it was observed that some characteristics such as color, texture and drill resistance differed in its various regions. Pubic bone was darker and more resistant when compared with iliac bone.…”
Section: Discussionmentioning
confidence: 99%
“…values may result in higher failure rates due to a distinctive bone compression with microdamages 24 or even to mini-implant fracture at torque moments above 200 Nmm. 18 As a consequence, it seems important to adapt the clinical procedure to the local circumstances (bone quality, thickness of the gingiva, available space) and the insertion procedure (transgingival vs submucosal insertion).…”
Section: Discussionmentioning
confidence: 99%
“…18 For mini-implants with a diameter of 1.6 mm, an insertion torque of 5 Ncm to 10 Ncm (50 Nmm to 100 Nmm) seems to be favorable to minimize the risk of failure. 12,13 Higher values may result in higher failure rates because of a distinctive bone compression with microdamages 24 or may even cause mini-implant fracture. 18 To summarize, it seems very important (1) to know the factors affecting the insertion torque/primary stability exactly and (2) to adapt the clinical procedure with the goal of achieving an insertion torque in the recommended range.…”
Section: Introductionmentioning
confidence: 99%
“…11 While some recommend 5-10 Ncm insertion torques, 12 in general, higher insertion torque would produce greater primary stability. 13,14 But, excessive insertion torque produces potential failure due to bone necrosis, 15 microdamage, 16,17 or MSI fracture during insertion. 18 To avoid excessive insertion torque, one approach is to change the shape of the MSI.…”
Section: Introductionmentioning
confidence: 99%